Detection of mostly viral pathogens and high proportion of antibiotic treatment initiation in hospitalised children with community-acquired pneumonia in Switzerland – baseline findings from the first two years of the KIDS-STEP trial (Swiss Medical Weekly, 2023)
AIMS OF THE STUDY: Globally, since the introduction of conjugate-vaccines against encapsulated bacteria, respiratory viruses have caused most hospitalisations for community-acquired pneumonia. The aim of this study was to describe pathogens detected and their association with clinical findings in Switzerland.METHODS: Baseline data were analysed for all trial participants enrolled between September 2018 and September 2020 into the KIDS-STEP Trial, a randomised controlled superiority trial on the effect of betamethasone on clinical stabilisation of children admitted with community-acquired pneumonia. Data included clinical presentation, antibiotic use and results of pathogen detection. In addition to routine sampling, nasopharyngeal specimens were analysed for respiratory pathogens using a panel polymerase chain reaction test covering 18 viral and 4 bacterial pathogens.RESULTS: 138 children with a median age of 3 years were enrolled at the eight trial sites. Fever (obligatory for enrolment) had been present for median 5 days before admission. Most common symptoms were reduced activity (129, 93.5%) and reduced oral intake (108, 78.3%). Oxygen saturation